Upaya Meningkatkan Kemampuan Bahasa Melalui Permainan Detektif Huruf Di Tk Negeri Desa Karangwuni Polokarto Sukoharjo Tahun Ajaran 2016/2017 - Nur yuliyanti, Irma; , Drs. Haryono Yuwono,SE., M.Pd (2017)
This study aims to determine the improvement of language skills through play detective letters in TK Negeri Desa Karangwuni Polokarto Sukoharjo. This improvement is evidenced by the increase in the percentage of the language skills before actions or pre-cycle development to the second cycle, when the pre-cycle development of children language reached 56.88% of the target set of 50%, cycle 1 of 69, 99% of the target set of 60% and the second cycle of 87.44% of the specified targets of 80%, with language skills can be improved through detective game. Based on the results of these calculations can be concluded that language skills can be enhanced through the letter detective game in TK Negeri Desa Karangwuni Polokarto Sukoharjo. Keywords: letter detective game, improve their language skills